Optimalisasi Pemanfaatan Media Sosial untuk Pemasaran Produk UMKM di Krembangan Selatan: Sebuah Program Pengabdian Masyarakat - Achmad Roziqin; Siti Binik Rusmiati; Kofifah Mega Parawansa; Cevin Dwi Pradana; Zakiyyah Adinda; Nurkholis Majid (Pusat Riset dan Inovasi Nasional, 2025)
This community service aims to maximize the use of social media as a marketing tool for Micro, Small, and Medium Enterprises (MSMEs) in the South Krembangan area. Many MSMEs in this area have excellent product potential, but remain adept at leveraging digital platforms to increase their market reach. Through case studies and in-depth interviews with selected MSMEs, we will uncover the best practices, obstacles encountered, and specific needs related to digital marketing. Based on the results of the case studies and interviews, this program will be implemented through three main pillars: outreach, interaction forums, and mentoring. Outreach will emphasize basic education on various types of social media relevant to marketing, important features to utilize, and potential benefits. Furthermore, the interaction forums will provide opportunities for MSMEs to share experiences, challenges, and solutions related to digital marketing, foster collaborative learning, and build networks. Finally,mentoring will be provided so that MSMEs can create engaging content, manage social media accounts effectively, understand simple analytics, and design digital marketing campaigns tailored to their product characteristics. This program is expected to increase the visibility of MSME products in South Krembangan, expand market share, and contribute to increasing their income and business sustainability.